Health benefits of social participation interventions among community-dwelling older persons: a review article - Ibrahim, Amirah Fatin; Tan, Maw Pin; Teoh, Gaik Kin; Muda, Siti Mariam; Chong, Mei Chan (Taylor & Francis, 2021)
Background: Social disengagement among older persons may result from accumulated physical impact and social stressors experienced throughout life. Conversely, interventions that enhance social participation addresses social isolation with positive influences on health. This article, therefore, aimed to review the range of published studies that evaluated the health benefits of interventions on social participation among community-dwelling older persons.Method: We conducted a search using the databases CINAHL, MEDLINE, EBSCOhost, PubMed, ProQuest, SAGE, ScienceDirect, SpringerLink, Web of Science, and Open repository/archive.Results: Twenty-five studies from Asia, Europe and America were selected. Included articles described randomized controlled trials (9), quasi-experimental studies (9), mixed-methods studies (2), participatory action research (3), and community-based intervention research (2). Social interventions described are group or cultural activities, personal/group monitoring and discussion, and communications devices. Intervention designed utilized theories, models, concepts, principles, and evidence from published literature.Conclusion: Most social intervention studies evaluating health outcomes have been conducted in North America and Western Europe. Group-based activities were most commonly employed, but personal/group discussions, home visits and technology-based interactions have also been used. While social isolation is now a widely accepted risk factor for ill-health, research evidence for improvement of health through reduction of social isolation remains limited.